Re-evaluating natural intelligence in the face of ChatGPT - LIM, Elvin T. (Institutional Knowledge at Singapore Management University, 2023)
How will new technologies impact the nature of higher education? Before ChatGPT, the world witnessed major shifts led by innovations in information storage and transmission. Papyrus in ancient Egypt, the Gutenberg press in 15th-century Europe, and the internet in the 20th century were all milestones in the mass dissemination of knowledge.